2020
DOI: 10.1152/japplphysiol.00701.2019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated local heat therapy on skeletal muscle structure and function in humans

Abstract: Introduction Short‐term exposure to heat stress has been shown to enhance muscle strength and elicit mitochondrial adaptations in human skeletal muscle. We recently documented that exposure to five sessions of heat therapy (HT) accelerates the recovery of fatigue resistance following exercise‐induced muscle damage in humans. However, the long‐term impact of repeated exposure to local heat stress on contractile function and skeletal muscle structure remains unknown. The purpose of the present study was to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 38 publications
(47 reference statements)
1
40
0
Order By: Relevance
“…Consistently, we found no effect of SL on upstream kinases (i.e., AMPK, p38 MAPK) regulating the mitochondrial biogenesis program. Instead, our findings align with Kim et al (2020) , who demonstrated no effect on mitochondrial adaptations following 8 weeks of localized (quadriceps) heat therapy. As discussed, such divergent findings may be attributed to differences in the duration of heating and changes in muscle temperature.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Consistently, we found no effect of SL on upstream kinases (i.e., AMPK, p38 MAPK) regulating the mitochondrial biogenesis program. Instead, our findings align with Kim et al (2020) , who demonstrated no effect on mitochondrial adaptations following 8 weeks of localized (quadriceps) heat therapy. As discussed, such divergent findings may be attributed to differences in the duration of heating and changes in muscle temperature.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, heating modality may also account for the observed differences. Specifically, pulsed shortwave diathermy utilized by Hafen et al (2018 , 2019) enables rapid and substantial deep tissue heating, and resultantly may be more effective at activating mitochondrial adaptations compared with superficial heat modalities as employed in the current and previous report ( Kim et al, 2020 ). Taken together, the current and previous findings ( Hafen et al, 2018 , 2019 ; Kim et al, 2020 ) tend to indicate muscle temperature, core temperature and duration of stimulus as important factors that determine the extent to which whole body or localized heat stress may be beneficial.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Connective tissues may also change viscosity and density in response to heat, thereby improving the range of movement and enhancing tissue extensibility. Recent evidence also suggests that localized, repeated heat therapy may promote an angiogenic environment and enhance muscle strength [17,18,29,41,42]. One advantage of superficial heat therapy is its safety profile.…”
Section: Overview Of Heat Therapy: Superficial/deep Treatment Modalitiesmentioning
confidence: 99%